IMPROVING THE VOCABULARY MASTERY THROUGH WORD-CONNECTION GAME - tanasy, novalia (ETERNAL (English, Teaching, Learning, and Research Journal), 2019)
Many students face difficulties to express their mind, ideas and feelings because lack of vocabulary. This fact makes them loose the point of information and lead them to the thought that English is a difficult subject, till even frustration. This is why every student must master vocabulary, because when they do, it will be easy for them to master the four language skills. This reasearch aimed to find (1) whether the use of Word-Connection game significantly improved the students vocabulary mastery of the first grade students of English Education in Universitas Muslim Maros on academic year 2018/2019, and (2) their attitudes toward the use of this game. Method of this research was experiment with 2 classes as the subjects. It employed 30 numbers of vocabulary test then analyzed by using inferential statistic SPSS program 25.0 and 20 numbers of close-ended questions questionnaire to find out their attitude towards the use of Word-Connection game. Result of the calculation data said that the mean score improved significantly at the experiment group from 3.476 to 8.356, but at the control group only from 3.950 to 4.550. Standard deviation at experiment group decreased from 1.2444 to 0.9238 and at control group from 1.5472 to 1.7604. Range on normalized gain score at the experiment group was 0.37, smaller than control group which was 0.43. Standard deviation on normalized gain score at experiment group was 0.115511 whereas at control group was 0.11075. Furthermore, data which were collected from questionnaire indicated that the students had positive attitude toward the use of Word-Connection game with mean score 82.68. Findings above concludes that the use of Word-Connection game can improve the students vocabulary mastery at the experiment group.